I saw democracy murdered - Russell, Sam, 1915-2010, author.
1 online resource.
Keywords: "I Saw Democracy Murdered is the memoir of Sam Russell (1915-2010), a communist journalist and a British volunteer with the anti-fascist Republican forces in the Spanish Civil War. The book covers his experiences during the Spanish Civil War, his time as a journalist at The Daily Worker and The Morning Star newspapers, and his later disillusionment with Stalinism. In his capacity as a journalist, Russell travelled extensively and was frequently a front-row spectator at significant historical events, from the formerly occupied Channel Islands at the end of World War II to the show trials of communists in Eastern Europe in the 1950s. His report as Moscow correspondent on Nikita Khruschev's 'secret speech' condemning the crimes of Stalinism was lacerated by his newspaper's editor, as was his interview with the legendary revolutionary leader, Che Guevara. Sam, whose friends included Donald MacLean, the British diplomat who spied for the Soviet Union during the Cold War, also reported from Budapest in 1956 and Prague in 1968 during the Warsaw Pact invasions of Hungary and Czechoslovakia, and from North Vietnam during the Vietnam War, and in 1973 he witnessed the assault on Chilean President Salvador Allende's palace that signalled the start of the CIA-backed military coup. Sam's story was told to Colin Chambers and Chris Myant and has been edited by Colin Chambers. This autobiographical account of a fascinating life will be essential reading for scholars and activists with an interest in the Spanish Civil War, the history of communism, and British radical history"--